Using the Digits-In-Noise Test to Estimate Age-Related Hearing Loss. Issue 5 (September 2016) - Koole, Arne; Nagtegaal, A. Paul; Homans, Nienke C.; Hofman, Albert; Baatenburg de Jong, Rob J.; Goedegebure, André
Abstract : Objective: Age-related hearing loss is common in the elderly population. Timely detection and targeted counseling can lead to adequate treatment with hearing aids. The Digits-In-Noise (DIN) test was developed as a relatively simple test to assess hearing acuity. It is a potentially powerful test for the screening of large populations, including the elderly. However, until to date, no sensitivity or specificity rates for detecting hearing loss were reported in a general elderly population. The purpose of this study was to evaluate the ability of the DIN test to screen for mild and moderate hearing loss in the elderly. Design: Data of pure-tone audiometry and the DIN test were collected from 3327 adults ages above 50 (mean: 65), as part of the Rotterdam Study, a large population-based cohort study. Sensitivity and specificity of the DIN test for detecting hearing loss were calculated by comparing speech reception threshold (SRT) with pure-tone average threshold at 0.5, 1, 2, and 4 kHz (PTA0.5, 1, 2, 4 ). Receiver operating characteristics were calculated for detecting >20 and >35 dB HL average hearing loss at the best ear. Results: Hearing loss varied greatly between subjects and, as expected, increased with age. High frequencies and men were more severely affected. A strong correlation ( R = 0.80, p < 0.001) was found between SRTs and PTA0.5, 1, 2, 4 . Moreover, 65% of variance in SRT could be explained by pure-tone thresholds. For detecting mild or moderate hearing loss, receiver operating characteristics showed areas under the curve of 0.86 and 0.98, respectively. Conclusions: This study demonstrates that the DIN test has excellent test characteristics when screening for moderate hearing loss (or more) in an elderly population. It is less suited to screen for mild hearing loss. The test is easy to complete and should be suitable for implementation as an automated self-test in hearing screening programs. Ultimately, when combined with active counseling, hearing screening could lead to higher hearing aid coverage in the hearing impaired elderly. Abstract : The Digits-In-Noise (DIN) test has been proposed as a simple method to screen for hearing loss. In this large cohort study, as part of the Rotterdam Study, the DIN test was evaluated for its ability to screen the elderly for mild and moderate hearing loss. The DIN test had a strong correlation with pure-tone thresholds. Sensitivity and specificity were calculated by comparing speech-reception thresholds with pure-tone thresholds. Test characteristics were excellent for detecting moderate hearing loss. Implementing the DIN test in screening programs could lead to more awareness of hearing loss and potentially to higher rehabilitation rates in the hearing impaired elderly.